Study of The Effect of Sugar and Lime Juice Proportion on the Quality of Starf Ruit Sorbet - Hermawan Seftiono; Gracecilia Yohanna Panjaitan; Inanpi Hidayati Sumiasih (Hasanuddin University, 2020)
Star fruit is a non-seasonal fruit that can be harvested three to four times a year. One possible way to process a star fruit is to make it into sorbet. Additional ingredients such as sugar and lime juice will help improve the quality of star fruit sorbet. The purpose of this study was to acquire the best formulation of honey star fruit sorbet by adding sugar and lime juice and to find out the effect of different concentration of sugar and lime juice on the level of predilection, physical traits, level of vitamin C, and antioxidants activity. This study consisted of two phases; the production of lime essence in phase one and the making of star fruit sorbet in phase two as the main study. The result of best formulations selected based on organoleptic test of panellists’ level of predilection were formulation of 150 g sugar + 30 g lime, 90 g sugar + 60 g lime, and 120 g sugar + 60 g lime. Analysis of variance results indicated different formulation of star fruit sorbet had significant effect (P<0.05) on colour, flavour, aroma, and overall but showed no difference on the texture of star fruit sorbet. Overall, the best formulation was 150 g sugar + 30 g lime juice with overrun score of 23.52%, pH 4.20, sugar content of 26.85 oBrix, melting time of 43.16 minutes, vitamin C content of 0.968 mg, and antioxidant activity of 320.86 ppm.Keyword: antioxidant activity; hedonic test; organoleptic test.